Chronic Inflammation and Malignancy in Ulcerative Colitis. (24th February 2011) - Sunkara, Sai; Swanson, Garth; Forsyth, Christopher B.; Keshavarzian, Ali
Abstract : Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) associated with multiple colonic and extraintestinal complications, the most severe being the development of colorectal cancer (CRC). Compared to the general population, there is an increased risk of CRC associated with UC. Although the pathogenesis of CRC in UC is unknown, most studies have linked it to long-standing inflammation as well as other risk factors such as duration of disease, extent of inflammation, family history of CRC, and coexisting conditions such as primary sclerosing cholangitis (PSC). UC is a life-long disease for which patients enter a vigilant screening program which includes surveillance colonoscopy to promote early detection of CRC yet some controversies exist regarding the cost effectiveness of surveillance colonoscopy and improving survival. Newer modalities such as chromoendoscopy, narrow band imaging, high definition colonoscopy, and confocal microscopy have aided in developing a more targeted approach for early detection of dysplasia in surveillance colonoscopy. This review focuses on the role of chronic colonic inflammation and dysplasia in development of UC-associated CRC and current methods of screening, detection, chemoprevention, and treatment of UC-associated CRC.